Plant nematodes of agricultural importance : - Bridge, John (Manson Pub., 2007)
The book deals with plant nematode pests, focusing on above-ground symptoms, and below-ground causes: It offers knowledge about biology and parasitism, the various types of parasitic nematodes, and the ways in which they attack plants; It also covers grain legumes, vegetables, flowers, cereals, root and tuber crops, tree, plantation and cash crops. For each nematode, concise information is provided on its distribution, symptoms and diagnosis, damage and economic importance, management and identification. Finally, this is the common investigative methods used in nematology.